The Relevance of Bibliometric Indicators and Academic Criteria in Economics - Madalina Dumitru (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question - Are the bibliometric indicators included in the Journal Citation Reports (JCR) and the academic criteria in the Economics domain relevant from the point of view of the assessment of the quality of the research activity? Motivation - This study is motivated by the fact that the research landscape changed significantly during the last years, with the growth of open access publishers. In addition, the number of journals and the value of the bibliometric indicators included in the JCR are growing. As such, the relevance of the academic criteria is affected. Data - Data for this study were collected from the JCR for 50 journals edited by five publishers. Tool - An original database created by the author starting from the JCR was used as a tool for the present study. Findings - The results have shown that the fast-publish editor selected for the study registers a high number of self-cites within the publishing house, and also that the self-cites are mostly directed towards the recently published papers, so that they influence the value of the bibliometric indicators. Practical implications - The importance of the findings of such research stems from providing evidence on the rise of a new type of publisher, open access, fast growing, fast publishing, fast citing. Also, the behaviour of Romanian academics and the criteria they have to comply with in their careers are affected. The results have implications for the authorities setting the criteria for academics.
Keywords: A10; A19; 650; self-cites; Clarivate; fast research; fast publish; fast cite; academic publishing